Analysis of undesired environmental behavior among Chinese undergraduates. (20th September 2017) - Chen, Feiyu; Chen, Hong; Guo, Daoyan; Long, Ruyin
Abstract: In the field of environmental behavior, systematic definitions and deep analysis of behaviors that negatively affect the environment are rare. In this study, the concept of undesired environmental behavior (UEB) was defined based on negative behavioral characteristics. Qualitative analysis and factor analysis were used to construct and verify the two-factor structure of UEB (active participant behavior and passive disregard behavior). Furthermore, from the perspective of behavioral motivation, the behavior was divided into three categories: spontaneous behavior, following behavior, and defensive behavior. Using survey data of 1974 undergraduates in China, we found that UEB occurred with high frequency, accounting for 53.5% of all reported behaviors. There were no significant differences in UEB in relation to gender or whether the student was an only child or not. Defensive-disregard behavior was more frequently observed among "good students" who had attained higher levels of scholarship, and defensive-participant behavior was more likely to occur as undergraduates' grades increased. In addition, UEB among undergraduates decreased significantly in relation to different school locations, different monthly family incomes, and different monthly living expenses. Specifically, undergraduates in East China in high-income families more frequently displayed spontaneous-disregard behavior and following-participant behavior; undergraduates with high living expenses more frequently performed spontaneous-participant behavior and following-participant behavior. Finally, suggestions are provided for managing and reducing UEB. Highlights: The connotation of undesired environmental behavior (UEB) was proposed and analyzed. The conceptual structure of UEB was constructed from the perspective of motivation. UEB differed significantly in social demographic variables. Administrative and educational strategies for intervening in UEB were provided.